2011
DOI: 10.3892/mmr.2011.623
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ROS and p38MAPK contributes to chemical hypoxia-induced injuries in PC12 cells

Abstract: Abstract. The present study investigated whether there is an interaction between reactive oxygen species (ROS) and p38 mitogen-activated protein kinase (MAPK) during chemical hypoxia-induced injury in PC12 cells. The results of the present study showed that cobalt chloride (CoCl 2 ), a chemical hypoxia agent, markedly induced ROS generation and phosphorylation of p38MAPK, as well as neuronal injuries. N-acetylcysteine (NAC), a ROS scavenger, blocked CoCl 2 -induced phosphorylation of p38MAPK. In addition, SB20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To investigate the key factors involved in oxidative stress promoting EV release, we first evaluated secreted EV concentration under different ROS levels. Our study utilized hydrogen peroxide (H 2 O 2 ) treated cells, a CoCl 2 hypoxia model (Lan et al., 2012 ), and a stable HBV replication model (HepG2.2.15 cell line) (Yuan et al., 2016 ) as high ROS conditions, while the ROS scavenger N‐acetyl cysteine (NAC) was used to abolish increased ROS (Figure S1a‐c ). Nanoparticle tracking analysis (NTA) (Figure 1a‐c ) and changes in EV markers (Figure 1d‐f ) revealed that oxidative stress promotes EV release in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the key factors involved in oxidative stress promoting EV release, we first evaluated secreted EV concentration under different ROS levels. Our study utilized hydrogen peroxide (H 2 O 2 ) treated cells, a CoCl 2 hypoxia model (Lan et al., 2012 ), and a stable HBV replication model (HepG2.2.15 cell line) (Yuan et al., 2016 ) as high ROS conditions, while the ROS scavenger N‐acetyl cysteine (NAC) was used to abolish increased ROS (Figure S1a‐c ). Nanoparticle tracking analysis (NTA) (Figure 1a‐c ) and changes in EV markers (Figure 1d‐f ) revealed that oxidative stress promotes EV release in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…CoCl 2 is a well-known chemical that mimics hypoxia; it causes the same effects in several aspects in various cultured cells, including loss of mitochondrial membrane potential, increase the release of ROS that causes cell death, and increased expression of HIF-1α and p53, which are implicated in the apoptotic pathway [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…CoCl 2 significantly increased the production of ROS, phosphorylated p38 mitogen-activated protein kinase (MAPK), and damaged neurons [ 15 ]. It has been suggested that the ROS produced by cobalt chloride have a role in the signaling mechanism that stabilizes the transcription factor HIF-1α during hypoxia.…”
mentioning
confidence: 99%
“…ROS is a well known etiological factor associated with oxidative stress leading to cell death via apoptosis in a variety of cell types [ 37 , 38 , 39 , 40 ], and such effects can be blocked or delayed by a wide variety of antioxidants [ 41 ]. Mitochondria-dependent apoptotic pathways are involved in glutamate-induced cytotoxicity in PC 12 cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%